1991
DOI: 10.1007/bf01758635
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic arsenic compounds: are they carcinogenic, mutagenic, teratogenic?

Abstract: This review examines and evaluates the literature on the ability of inorganic arsenic compounds to cause cancer in humans and laboratory animals. The epidemiological data that supports the position that inorganic arsenical derivatives are carcinogenic in humans is convincing and difficult to deny because of their consistency. These data are from studies of different occupational exposures such as smelter and pesticide workers, as well as from studies of drinking water, wines and medicinal tonics that contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 121 publications
0
11
1
Order By: Relevance
“…However, the levels of zinc observed in this experiment surpassed those determined in sheep that had been fed emissions from a copper or a zinc plant, as reported by Bfreg et al (1991) and Reif et al (1989), respectively. In contrast to the results achieved in this work, several authors reported positive clastogenic effects of some of the metals (arsenic, cadmium, lead, copper and zinc) or their compounds found in emissions (Wong, 1988, Goldman & Dacre 1991, Magos 1991, Coogan et al 1992), on the basis of testing the individual elements under in vitro conditions. As a criterion of mutagenic activity, chromosome break evaluations were also employed by Bockov et al (1975( ), Brogger (1982 and Lojda & Mrfiz (1982).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the levels of zinc observed in this experiment surpassed those determined in sheep that had been fed emissions from a copper or a zinc plant, as reported by Bfreg et al (1991) and Reif et al (1989), respectively. In contrast to the results achieved in this work, several authors reported positive clastogenic effects of some of the metals (arsenic, cadmium, lead, copper and zinc) or their compounds found in emissions (Wong, 1988, Goldman & Dacre 1991, Magos 1991, Coogan et al 1992), on the basis of testing the individual elements under in vitro conditions. As a criterion of mutagenic activity, chromosome break evaluations were also employed by Bockov et al (1975( ), Brogger (1982 and Lojda & Mrfiz (1982).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the above disputed data for humans, arsenic has never been proven to be a carcinogenic agent in rodents, either through dietary intake, inhalation, injection or skin painting (Fan, 1990;Goldman and Dacre, 1991). In more than 30 attempts to induce cancer in experimental animals, one study either failed to find cancer or, where cancer was induced, another recognised carcinogenic agent was always found.…”
Section: Toxic Carcinogenic Mutagenic and Teratogenic Effects Of Armentioning
confidence: 99%
“…Chronic exposure to arsenic compounds leads to skin and lung cancer in exposed humans, while animal studies failed to detect a carcinogenic potential (for review, see Goldman & Dacre 1991, Bates et al 1992. Regarding the genotoxicity, arsenic is not mutagenic in bacterial test systems nor in mammalian cells.…”
Section: Arsenicmentioning
confidence: 99%